Attitudes and cooperation: does gender matter in community-based forest management?. (19th December 2016) - Ray, Biswajit; Mukherjee, Promita; Bhattacharya, Rabindra N.
Abstract: Does gender matter in people's attitudes and cooperation in community-based natural resource management? If so, how do gender differences in conservation-related attitudes help or hinder sustaining the commons? Since biases ingrained in community norms and expectations often exclude women from decision making in co-management, it is imperative to find plausible answers to these queries in order to understand gender relations and cooperation in co-management. To this end, the authors conducted psychometric surveys and trust experiments on 196 forest-dependent households in West Bengal, India during 2009–2010. The findings suggest that, despite an overall negative perception about women's involvement in co-management, women are more conservation friendly and pro-social than men. It is also noticed that forest biomass and forest incomes as the indicators of sustainability have increased in those forest communities where women's proportional strength as decision makers is greater and people hold an overall positive conservation attitude.